Photographic capture of medium-sized mammals in ecological restoration experimental plots in a cattle pasture landscape in Los Tuxtlas, Veracruz, Mexico - Zagal-García, Kenia Vanessa; Martínez-Garza, Cristina; Valenzuela-Galván, David (Instituto de Ecología, A.C., 2022)
Background and Aims: In an experiment initiated in 2006 in an induced pasture, within a landscape dominated by tropical rainforest, in Los Tuxtlas, Veracruz, 24 fenced plots with three restoration treatments were established. Our objective was to determine with camera trapping, which species of medium or large terrestrial mammals (≥1 kg in weight), and with what frequency, visited the plots 12 years after the establishment of the experiment.Methods: Camera traps were used in 18 of the 24 plots. Two censuses were carried out, one in the rainy season of 2018 and the other in the dry season of 2019. The number of species and the independent photographic records of each one were determined for each treatment (plots excluded from cattle: a) with no addition of plants -natural succession-; with tree plantations, b) dispersed by wind, and c) dispersed by animals) and each sampling season.Key results: The total sampling effort was 290 camera trap days. For the rainy season, 12 photographs and four videos of opossum (Didelphis spp.), nine-banded armadillo (Dasypus novemcinctus) and Mexican agouti (Dasyprocta mexicana) were obtained. For the dry season, the armadillo was recorded in 10 photographs and five videos. There were few records of medium-sized mammals, compared to photo trapping in conserved forest in the area and only in seven of the 18 sampled plots. Overall, there were more records in plantations than in natural succession, and this was more evident in the rainy season.Conclusions: The response of medium-sized terrestrial mammals to restoration seems to be slower than recorded for other faunal groups (e.g., bats). To assess the recovery of ecological functionality that includes the ecological roles played by medium-sized mammals in this experiment, monitoring effort should be continued and expanded.